WHO’S WATCHING THE WEB SERIES IN INDIA AND WHY? – A VALUES BASED SEGMENTATION OF THE GRATIFICATIONS DERIVED - Pooja Valecha (International Journal of Modern Agriculture, 2021)
This study delves into a very popular phenomenon; the web series- in an environment of increasing media fragmentation and the battle for viewer attention. Through this study, an attempt has been made to understand these viewers better, going beyond their pure demographics and delving into their identities in terms of their value orientations. It has been proved through various studies that personal values have an effect on the viewing behaviour and the gratifications that a person desires to derive from that experience. Therefore it is also attempted to match these gratifications with the value sets of people. Thus, leading to a segmentation of the viewers of web series soaps on the basis of their values and linking each of these segments with the gratifications derived by each of them respectively. Thus, the proposition of moving the concept of uses and gratifications beyond causality to a tool of segmentation and beyond has been underscored. Also the study attempts to help in providing the OTT platforms and the advertisers, a glimpse into the mind-sets of the various sets of their target groups when they are consuming their ‘brand’ and thus help to build a better connect with the consumers.